A STATE-OF-THE-ART REVIEW OF TOURIST DECISION-MAKING LITERATURE - Le, Dung; Le, Thai Phong (Journal of International Economics and Management, 2018)
Decision-making theories in tourism can be classified into three groups based on their underlined assumptions: rational choice, affect-driven and dual-process theories. Rational choice theories are the dominant framework in many fields including economics, political science, finance, marketing and tourism. Consumers are considered as “rational-decisionmakers” who evaluate available options by rational thinking. In contrast, the affect-driven theories assume that tourists are hedonic decision-makers and their choice is influenced and guided by affective factors (i.e., emotions, feelings). Dual-process theories reconcile these two opposite approaches by proposing a dual-system of decision-making: System 1 related to automatic, emotional, non-conscious process, and System 2 involving rational thinking. This review paper provides a general picture of how tourism decision-making literature has been developed with a focus on the latest advancement, dual-system theories. Tourism marketers may find this paper beneficial in understanding tourist behaviours, in particular, tourists’ destination choice. Traditional marketing focusing only on rational factors (comparative messages) can be a dead-end approach, experiential marketing has become the new trends. By advancing our knowledge of tourist decision-making, this paper provides useful guidelines for tourism marketers in designing tourist experiences and promoting tourism destinations.